Hysteresis Modeling for Torque Control of an Elastomer Series Elastic Actuator - Kim, Dong-Hyun; Oh, Jun-Ho (IEEE/ASME transactions on mechatronics, 2019)
Recent research on humanoid robot actuators has shown that the use of series elastic actuators (SEAs) is necessary for accurate and robust torque control. Among the numerous implementations of an SEA, using a spring as an elastomer is considered to be the most suitable. However, a major disadvantage of this method in terms of torque control is the hysteresis of the elastomer. Although various hysteresis modeling methods have been studied to resolve the hysteresis problem of an elastomer, they are not sufficiently accurate to perform torque control. Therefore, we propose a hysteresis model and compensation method to estimate torque based on deformation for the hysteresis of an elastomer SEA to resolve the problems encountered in previous studies. Torque control is evaluated with the proposed hysteresis compensation method. Torque measurements obtained using the proposed hysteresis model improve the maximum error by up to 10% compared with that of Hooke's law, which has a maximum error of 25%. Torque control of an elastomer SEA can be performed with improved accuracy by using the proposed hysteresis model and compensation method.